Effect of Parity and Type of Birth on Reproduction Performance of Garut Ewes in Indonesia - Wijayanti, Dwi; Ardigurnita, Firgian; Frasiska, Nurul; Fatihul Ihsan, Nurul Farhan; Darusman, Asep Dudung (Buletin Peternakan, 2025)
Garut sheep is one of the superior sheep breeds originating from Garut, West Java, Indonesia. Garut sheep have a good reproductive system with a relatively high birth rate. This facilitates the process of breeding and developing sheep populations. However, it is not yet known whether there is an influence of non-genetic factors (parity and birth type) on reproduction (liiter size, lambing interval, birth weight, and weaning weight) of Garut sheep. Therefore, this study aims to determine the relationship of non-genetic factors on reproductive traits of Garut ewes. The total number of female Garut sheep used was 327 with the criteria of having given birth. The results showed that the average litter size, lambing interval, birth weight, and weaning weight were 1.87 heads, 118 days, 2.73 kg, and 12.86 kg, respectively. The 3rd parity had the highest litter size and a shorter kidding interval than other parities. In addition, the type of birth also has a significant effect, namely the number of kids triple effect on the long lambing interval. Non-genetic factors affected the reproductive performance of Garut sheep.